PVP‐templated novel fluorescent Ag nanomaterials synthesis and its application to bioimaging. (1st June 2018) - Nie, Furong; Ga, Lu; Ai, Jun; Wang, Yong
Abstract : Herein, the work reports a novel approach to silver nanoparticles (AgNPs) with high fluorescence emission and smooth sphere morphology are prepared by a facile template synthesis strategy using polyvinyl pyrrolidone k‐30 as a novel protective agent. It shows excellent fluorescence property and special morphology, and thus has great potential for the applications in biological imaging. It is also precise and highly reproducible in determining Cd 2+ in real samples such as natural mineral water, tap water, milk and sewage with recoveries ranging from 90 to 111%, indicating the wide practical application to samples suspected of Cd 2+ exposure.